Nouveaux indices de fréquentation du Val d’Orléans (Loiret) par les premiers mésolithiques - Sandrine Deschamps; Morgane Liard; Johannes Musch (Revue Archéologique du Centre de la France)
Two recent field campaigns have revealed the presence of early Mesolithic settlement in the Loire valley near Orléans (Loiret, France). The first collected evidence shows reasonably good preservation of the context for both sites, wich one only some 500 meters apart. Preliminary studies of the lithic assemblage combined with C14 dating confirm the identification of the remains as belonging to the early Mesolithic.Since these sites are in a high risk flood zone where building is forbidden, they are not threatened by development and therefore will not be excavated.These finds reopen the debate on the settlement of the Loire valley bottom in an early stage of the Holocene in social and cultural anthropology terms since they indicate recurrent occupations of the area.